2022
DOI: 10.3390/brainsci12121671
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Improved Thromboembolism-Based Rat Stroke Model That Meets the Latest Standards in Preclinical Studies

Abstract: The animal thromboembolic model of ischemia perfectly mimics human ischemic stroke which remains the leading cause of disability and mortality in humans. The development of new treatment strategies was therefore imperative. The purpose of this study is to improve the thromboembolic stroke model in rats in order to design experiments that use motor tests, and are in accordance with the 3R principles to prevent complications and maintain the same size of the infarct repeatedly. Tail vein dye application, a prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 58 publications
0
0
0
Order By: Relevance
“…In the present study, we also assess whether the positive biochemical and morphological changes observed under the influence of minocycline would translate into improved motor functions. In this regard, we would like to emphasize that our improved and minimally invasive animal model of ischemic stroke allows for motor tests to be performed after FCI [17]. The data from selected tests showed positive changes in gait, balance level, speed of movement, and leg strength.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…In the present study, we also assess whether the positive biochemical and morphological changes observed under the influence of minocycline would translate into improved motor functions. In this regard, we would like to emphasize that our improved and minimally invasive animal model of ischemic stroke allows for motor tests to be performed after FCI [17]. The data from selected tests showed positive changes in gait, balance level, speed of movement, and leg strength.…”
Section: Discussionmentioning
confidence: 95%
“…For this purpose, all the stroke animals underwent motor tests including the Horizontal Runway Elevated test (HRE), Grip Strength test (GST) and CatWalk™ XT. None of the animals had any health problems or complications following the procedures, and no animals were excluded from the tests, except for groups S1 and S1 + m, which had a short duration between general anesthesia and euthanasia, making it impractical to perform motor tests [17]. Using the GST test, we were able to analyze the strength of the front paws in stroke rats.…”
Section: Effect Of Minocycline On the Level Of Motor Performance In R...mentioning
confidence: 99%
See 3 more Smart Citations